2021
DOI: 10.3390/idr13010022
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Carriage of Methicillin-Resistant Staphylococcus aureus (MRSA) among Sickle Cell Disease (SCD) Children in the Pneumococcal Conjugate Vaccine Era

Abstract: The aim of this cross-sectional study was to investigate Staphylococcus aureus nasopharyngeal carriage epidemiology in relation to other nasopharyngeal bacterial colonizers among sickle cell disease (SCD) children about five years into pneumococcal conjugate vaccine 13 (PCV-13) introduction in Ghana. The study involved bacteriological culture of nasopharyngeal swabs obtained from 202 SCD children recruited from the Princess Marie Louise Children’s Hospital. S. aureus isolates were identified using standard met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 72 publications
6
12
1
Order By: Relevance
“…The highest proportion of S. aureus resistance was recorded against penicillin (100%). Previous studies in the country have also reported similar rates for the organism [ 30 , 53 , 54 , 56 , 57 , 58 ], and this may be due to the wide usage of the antibiotic. These studies additionally recorded similar antimicrobial resistance rates for the other antimicrobials investigated [ 30 , 53 , 54 , 56 , 57 , 58 ].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The highest proportion of S. aureus resistance was recorded against penicillin (100%). Previous studies in the country have also reported similar rates for the organism [ 30 , 53 , 54 , 56 , 57 , 58 ], and this may be due to the wide usage of the antibiotic. These studies additionally recorded similar antimicrobial resistance rates for the other antimicrobials investigated [ 30 , 53 , 54 , 56 , 57 , 58 ].…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies in the country have also reported similar rates for the organism [ 30 , 53 , 54 , 56 , 57 , 58 ], and this may be due to the wide usage of the antibiotic. These studies additionally recorded similar antimicrobial resistance rates for the other antimicrobials investigated [ 30 , 53 , 54 , 56 , 57 , 58 ]. Of particular interest is the high resistance displayed against cotrimoxazole in the current study, given its usage in prophylaxis.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Several studies conducted post PCV-13 vaccine rollout have also reported a higher prevalence of S. aureus nasopharyngeal colonization in relation to S. pneumoniae among children with SCD. 27,28 Therefore, the significantly higher carriage of S. aureus relative to S. pneumoniae among the participants of our study, as well as the presence of the other nasopharyngeal colonizers in low numbers, suggest the possible modification of the nasopharyngeal microbiota which can be a result of the use of pneumococcal prophylaxis in children with SCD. 29 This raises legitimate concerns, as S. aureus, although a commensal,…”
Section: Discussionmentioning
confidence: 66%
“…32,33 The prevalence of S. aureus within this study population was lower than reported in similar studies conducted in Ghana and Brazil where higher nasopharyngeal prevalence of 57.9% and 44.8%, respectively, have been documented. 27,28 The differences could be due to the nature of the study population, pneumococcal prophylaxis uses between the two populations, and the antimicrobial resistance pattern differences.…”
mentioning
confidence: 99%